Performance indicators in rugby union - Hughes, M.; Hughes, M. D.; Williams, J.; James, N.; Vuckovic, G.; Locke, D. (Journal of Human Sport & Exercise, 2012)
Team performance in rugby has typically been assessed through the comparison of winning and losing teams, however, the distinction between winning and losing was used as the sole independent variable. Thus potential confounding variables that may affect performance such as match venue, weather conditions and the strength of the opposition were not considered in this profile of a rugby team. Insufficient data currently exist regarding the development and measurement of performance indicators in rugby union. In particular, there is little research concerning position-specific performance indicators and their subsequent performance profiles. Research has also yet to establish the confidence to which these performance profiles are representative of an individual`s performance. The aim of this study was to exploit the unique opportunity of a large dataset from the 2011 World Cup, from analysts working with national teams, and combine this with examples of data taken from previous studies, in an attempt to identify a more focused direction for the analysis of rugby union. The majority of data collected in the results section were during and after the 2011 Ruby Union World Cup in New Zealand by professional analysts working for a firm called PGIR, which has the analysis franchise for the England RFU. All data were checked for accuracy and reliability by cross-referencing actions to post event from video. It was concluded that in a complex dynamic interactive team sport, such as rugby, that simple analyses of frequency data, although informative, cannot possibly be expected to model this very difficult and multivariate problem.